Global Justice Protest Events and the Production of Knowledge about Differences - Daro, Vinci (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractRecent social movement activities – in particular, transnationally-coordinated global justice mobilizations – require participants to work across substantial differences in languages, cultural backgrounds, political visions, and organizing traditions. Negotiating such differences is an active, adaptive, and learning-intensive process. In contrast to more institutionalized settings such as schools and workplaces, where tropes like “multiculturalism” figure prominently in treatments of “difference,” I argue that knowledge production in social movement settings cultivates a more intensely relational and dynamic disposition towards differences.